An updated survey of factors influencing property valuation accuracy in Australia. Issue 3 (15th February 2021) - Abidoye, Rotimi Boluwatife; Huang, Wei; Amidu, Abdul-Rasheed; Javad, Ashad Ali
Abstract : Purpose: This study updates and extends the current work on the issue of accuracy of property valuation. The paper investigates the factors that contribute to property valuation inaccuracy and examines different strategies to achieve greater accuracy in practice. Design/methodology/approach: An online questionnaire was designed and administered on the Australian Property Institute (API) registered valuers, attempting to examine their perceptions on the current state of valuation accuracy in Australia. The variables/statements from responses are ranked overall and compared for differences by the characteristics of respondents. Findings: Using mean rating point, the survey ranked three factors; inexperience valuers, the selection, interpretation and use of comparable evidence in property valuation exercise and the complexity of the subject property in terms of design, age, material specification and state of repairs as the most significant factors currently affecting valuation inaccuracy. The results of a Chi-square test did not, however, show a significant statistical relationship between respondents' profile and the perception on the comparative importance of the factors identified. Except for valuers' age and inexperience valuers and valuers' educational qualification and inexperience valuers and the selection, interpretation and use of comparable evidence in property valuation exercise. Also, the three highly ranked strategies for reducing the level of inaccuracy are: developing a global mindset, use of advanced methodology and training valuers on market forecasting skills. Practical implications: In order for valuers to provide state-of-the-art service to the public and to remain relevant, there is a need to accurately and reliably estimate valuation figures. Hence, the strategies highlighted in this study could be considered in a bid to reduce property valuation inaccuracy in practice. Originality/value: This study provides an updated overview of the issue of property valuation inaccuracy in the Australia valuation practice and examines the strategies to reduce it.